Entrepreneurship Education and Perception Change: The Preliminary Outcomes of Compulsory Entrepreneurship Course Experience in Turkey - Hilmi Bahadır Akın; Yavuz Demirel (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The importance of entrepreneurship is increasingly emphasized worldwide especially after the decline of centrally planned economic systems. The trends toward reducing the domination of governments in the economy put the entrepreneur, the sole actor who makes the markets work by starting and growing the businesses in any scale, in the center of the economy policies. In this context, the policies toward making entrepreneurship widespread and thereby achieve the aim of economic growth and wealth have been very common in both developed and developing countries for decades with a few exceptions worldwide. On the other hand, despite the increasing popularity of entrepreneur and entrepreneurship research, the number of entrepreneurs who undertake the risks of starting a business and grow it by innovation and thereby create new jobs is not that much in reality. It is not easy to motivate people to become entrepreneurs in the presence of different employment alternatives. So, the governments that chose free market economy system based upon entrepreneurship have been starting policies toward motivating individuals to choose entrepreneurship as a career alternative. Entrepreneurship education is one of the most common tools in this sense and has been used widely both in schools and out of school education. In this direction, programs supporting the entrepreneurs and people who have intentions to start their own businesses in Turkey is a government policy today. Aksaray University, a state university in Turkey, started a compulsory four hour Entrepreneurship course covering all undergraduate departments in Aksaray University. The senate of Aksaray University agreed on the compulsory entrepreneurship courses, which will be effective to all departments beginning from September 2012 -only selective for the departments which have curriculums determined centrally by the Ministry of Education or Higher Education Council of Turkey- and there is also an agreement between KOSGEB Republic of Turkey, Small and Medium Entreprises Development Organzation and Aksaray University to provide students a certificate which gives them the right to apply for certain financial incentives to start their own businesses. The aim of this research is to find out the perception change of students towards entrepreneur and entrepreneurship. A survey was conducted among 925 students who participated in these courses and who did not in Aksaray University and the results show that the compulsory courses have positive impacts on perceptions toward Entrepreneurship, along with the intention to start their own businesses. We hope that similar studies which will focus on the context of the course, the qualifications of the lecturers, the practices of students after graduation, their innovative behaviours in their business life will contribute to the Entrepreneurship Education field